Implikasi Indeks Pembangunan Manusia Dan Tingkat Pengangguran - Muhammad Attoriq (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research investigates the implications of the Human Development Index (HDI) and unemployment rate on a country's economic growth. Using empirical data and sophisticated analytical methods, this research evaluates the relationship between HDI, unemployment rate, and economic growth dynamics. We use a variety of econometric techniques to understand the complex interactions among these factors. It is hoped that the findings from this research will provide a deeper view of the factors that influence economic growth, enabling the formulation of more effective policies in terms of human development and unemployment reduction strategies.